Enantioselective separation of RS-mandelic acid using β-cyclodextrin modified Fe3O4@SiO2/Au microspheres. Issue 11 (15th May 2018) - Deng, Xiaojuan; Li, Wenbin; Ding, Guosheng; Chen, Xiaoping
Abstract : β-Cyclodextrin functionalized magnetic microspheres were prepared via a self-assembly method and applied for the enantioselective absorption of enantiomers. Abstract : Chiral magnetic microspheres show great potential in direct enantioseparation. Herein novel chiral magnetic microspheres were prepared by self-assembling β-cyclodextrin on magnetic Fe3 O4 @SiO2 /Au composite microspheres. The prepared materials were characterized by transmission electron microscopy (TEM), energy dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD), vibrating sample magnetometry (VSM) and Fourier transform infrared spectroscopy (FTIR). The results showed that the functional microspheres have a three-ply structure and high saturation magnetization. β-Cyclodextrin-immobilized magnetic Fe3 O4 @SiO2 /Au microspheres (Fe3 O4 @SiO2 /Au/β-CD) were applied in the direct chiral separation of RS -mandelic acid. The analysis results of HPLC revealed that the Fe3 O4 @SiO2 /Au/β-CD magnetic microspheres exhibited stronger enantioselective adsorption for R -mandelic acid than S -mandelic acid. The chiral selector functionalized magnetic microspheres are therefore expected to be an efficient and economical chiral separation method for use in further research.